1999
DOI: 10.1136/gut.45.2008.i9
|View full text |Cite
|
Sign up to set email alerts
|

Extradigestive manifestations of Helicobacter pylori gastric infection

Abstract: SummaryIn the past year, several studies have been carried out on the association between Helicobacter pylori infection and a miscellany of extradigestive diseases, such as cardiovascular, immunological, and various other pathologies. In particular, a higher prevalence of H pylori infection in patients aVected by ischaemic heart disease has been described and there is growing evidence for an association between H pylori and some autoimmune diseases. Moreover, recent studies have shown that various helicobacter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
78
0
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(80 citation statements)
references
References 41 publications
0
78
0
2
Order By: Relevance
“…The available data support an association between H. Pylori infection and ITP. 218 Studies have also shown that there is a significant increase in platelet count in patients with ITP after H. Pylori eradication. 220,222,223,224 Prevention of gastric cancer ACG recommends H. Pylori testing after endoscopic resection of early gastric cancer.…”
Section: Chronic Itpmentioning
confidence: 99%
“…The available data support an association between H. Pylori infection and ITP. 218 Studies have also shown that there is a significant increase in platelet count in patients with ITP after H. Pylori eradication. 220,222,223,224 Prevention of gastric cancer ACG recommends H. Pylori testing after endoscopic resection of early gastric cancer.…”
Section: Chronic Itpmentioning
confidence: 99%
“…Since the discovery in 1983 that the stomach could be colonized by bacteria [3], sufficient evidence has accumulated implicating H. pylori as a pathogen intimately related to benign stomach diseases, such us chronic gastritis and duodenal and gastric peptic ulcers [3], and malignant diseases, for example gastric cancer [4] and gastric MALT lymphoma [5]. Furthermore, during the last three decades following the discovery [3], approximately 50 extragastric diseases have been reported in medical specialties such as cardiology, dermatology, endocrinology, obstetrics and gynecology, pneumology, neurology, odontology, ophthalmology, otorhinolaryngology, pediatrics, and hematology [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20], the last of which is the subject of this review.…”
Section: Introductionmentioning
confidence: 99%
“…In the last years, H. pylori infection has been associated with some extradigestive pathologies, and expecially with organic and functional vascular disorders [9][10][11][12][13][14][15][16]. In particular, our group [11] recently reported a high prevalence of H. pylori infection, with particular regard to cytotoxic strains, in patients with migraine.…”
Section: Introductionmentioning
confidence: 99%